2017
DOI: 10.1007/s40279-017-0706-2
|View full text |Cite
|
Sign up to set email alerts
|

The Unexplored Crossroads of the Female Athlete Triad and Iron Deficiency: A Narrative Review

Abstract: Despite the severity and prevalence of iron deficiency in exercising women, few published reports have explored how iron deficiency interacts with another prevalent and severe condition in exercising women: the 'female athlete triad.' This review aims to describe how iron deficiency may interact with each component of the female athlete triad, that is, energy status, reproductive function, and bone health. The effects of iron deficiency on energy status are discussed in regards to thyroid function, metabolic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 254 publications
2
53
0
11
Order By: Relevance
“…The relationships between low EA and Triad components are well established,3 4 and this study supports that model. While there is less evidence supporting the other RED-S health consequences,5 our study supports the proposed associations between low EA and endocrine,30 31 metabolic,32 haematological,7 psychological,12 33 cardiovascular34 and gastrointestinal impairments35 of the RED-S model. Specifically, risks of metabolic, psychological and cardiovascular issues were more than two-fold greater in those with low EA than those with adequate EA.…”
Section: Discussionsupporting
confidence: 72%
“…The relationships between low EA and Triad components are well established,3 4 and this study supports that model. While there is less evidence supporting the other RED-S health consequences,5 our study supports the proposed associations between low EA and endocrine,30 31 metabolic,32 haematological,7 psychological,12 33 cardiovascular34 and gastrointestinal impairments35 of the RED-S model. Specifically, risks of metabolic, psychological and cardiovascular issues were more than two-fold greater in those with low EA than those with adequate EA.…”
Section: Discussionsupporting
confidence: 72%
“…This is due to a potential reduction in appetite, decreased metabolic fuel availability and impaired metabolic efficiency, leading to an increase in energy expenditure during exercise and rest 93. Iron deficiency may also interact with bone health via dysregulation of the GH/IGF-1 axis, hypoxia and hypothyroidism, in addition to playing an important role in thyroid function, fertility and even psychological well-being 93. Thus, LEA may be partially induced by, and may contribute to, iron deficiency 93.…”
Section: Health Effects Of Low Energy Availabilitymentioning
confidence: 99%
“…Iron deficiency may also interact with bone health via dysregulation of the GH/IGF-1 axis, hypoxia and hypothyroidism, in addition to playing an important role in thyroid function, fertility and even psychological well-being 93. Thus, LEA may be partially induced by, and may contribute to, iron deficiency 93. Surrogates for LEA have been correlated with haematological dysfunction, including low ferritin and iron deficiency anaemia, in adolescent and young adult female athletes 94…”
Section: Health Effects Of Low Energy Availabilitymentioning
confidence: 99%
“…Variables attributed to increased risk of RRI include poor nutrition habits, excessive training volume, history of past injury, poor lower extremity biomechanical characteristics of the athlete such as excessive knee internal rotation during running. 4,5,6,7,8,9,10,11,12 Several of these factors are modifiable and can be addressed and corrected with the proper strategies. For example, Fredericson et al demonstrated a reduction in iliotibial band syndrome symptoms after a hip abductor strengthening program.…”
Section: Introductionmentioning
confidence: 99%